Epigenetic switches in clag3 genes mediate blasticidin S resistance in malaria parasites. (19th July 2013) - Mira‐Martínez, Sofía; Rovira‐Graells, Núria; Crowley, Valerie M.; Altenhofen, Lindsey M.; Llinás, Manuel; Cortés, Alfred
Summary Malaria parasites induce changes in the permeability of the infected erythrocyte membrane to numerous solutes, including toxic compounds. In Plasmodium falciparum, this is mainly mediated by PSAC, a broad‐selectivity channel that requires the product of parasite clag3 genes for its activity. The two paralogous clag3 genes, clag3.1 and clag3.2, can be silenced by epigenetic mechanisms and show mutually exclusive expression. Here we show that resistance to the antibiotic blasticidin S (BSD) is associated with switches in the expression of these genes that result in altered solute uptake. Low concentrations of the drug selected parasites that switched from clag3.2 to clag3.1 expression, implying that expression of one or the other clag3 gene confers different transport efficiency to PSAC for some solutes. Selection with higher BSD concentrations resulted in simultaneous silencing of both clag3 genes, which severely compromises PSAC formation as demonstrated by blocked uptake of other PSAC substrates. Changes in the expression of clag3 genes were not accompanied by large genetic rearrangements or mutations at the clag3 loci or elsewhere in the genome. These resultsdemonstrate that malaria parasites can become resistant to toxic compounds such as drugs by epigenetic switches in the expression of genes necessary for the formation of solute channels.